2019
DOI: 10.1021/acs.jpca.9b10251
|View full text |Cite
|
Sign up to set email alerts
|

A Bond Charge Model Ansatz for Intrinsic Bond Energies: Application to C–C Bonds

Abstract: A simple Bond Charge Model is proposed to predict intrinsic bond energies. Model parameters can be derived from the topology of the Electron Localization Function and optimized geometries through classic considerations. Results for carbon-carbon covalent bonds are shown to be very accurate in different chemical environments. Insight can be extracted from the application of the model due to its elementary construction and simple mathematical formulation. The remarkable robustness of the fitted model highlights … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Indeed, a very good correlation (R 2 = 0.97) is found with respect to BE values calculated at the DFT B97XD/aug-qzvp level for bonds 1, 12, 19, 27, 26, 29, 34 of Tables 4 and 5. 19 Moreover,  tot can be compared with intrinsic bond energies computed from AIM critical point properties and bond paths (using, of course, correlated electron densities). 10,20 A rather good linear correlation is again obtained (R 2 = 0.94) with the set of bonds 1, 4, 8, 9, 12, 13, 18, 19, 26, 29, 30, 33, 34 of Tables 4 and 5.…”
Section: Dynamic Orbital Forces As Index Of Intrinsic Bond Energy and Tool For / Partitionmentioning
confidence: 99%
“…Indeed, a very good correlation (R 2 = 0.97) is found with respect to BE values calculated at the DFT B97XD/aug-qzvp level for bonds 1, 12, 19, 27, 26, 29, 34 of Tables 4 and 5. 19 Moreover,  tot can be compared with intrinsic bond energies computed from AIM critical point properties and bond paths (using, of course, correlated electron densities). 10,20 A rather good linear correlation is again obtained (R 2 = 0.94) with the set of bonds 1, 4, 8, 9, 12, 13, 18, 19, 26, 29, 30, 33, 34 of Tables 4 and 5.…”
Section: Dynamic Orbital Forces As Index Of Intrinsic Bond Energy and Tool For / Partitionmentioning
confidence: 99%
“…It was clearly shown that the original BCM model, as well as its updated version, in which it is coupled with the ELF [28], works well in as much the quantum mechanical correction represented by the exchangecorrelation term is considerably smaller than all the other contributions entering into the BCM energy. In this sense, it is remarkable to note that this model has recently been applied to the description of a variety of C-C bonds [29].…”
Section: Introductionmentioning
confidence: 99%